ACEH'S BORDERLINE DA'IYAH: WOMEN'S EMPOWERMENT STRATEGIES THROUGH GENDER-RESPONSIVE DA'WAH IN GAMPONG JAWA - Lailani Lailani; Khairul Habibi; Sakdiah Sakdiah (Kafa`ah: Journal of Gender Studies, 2025)
This study aims to analyze the role of female religious teachers in addressing women's issues in border areas, with a focus on Gampong Jawa, Kejuruan Muda District, Aceh Tamiang Regency. This area is a strategic border region vulnerable to external cultural influences and marked by various socio-religious issues, such as low Quran literacy, early marriage, and limited understanding among youth regarding Islamic law. The research method employed is a descriptive qualitative approach, utilizing data collection techniques including observation, in-depth interviews, and documentation. The research findings indicate that the presence of female religious educators significantly contributes to enhancing women’s understanding of Islam through Quranic study sessions, Quranic Education Centers, and other religious activities. Da'iyah are able to become figures accepted by the community in fostering the religious education of mothers and children, especially in terms of Quran literacy. Supporting factors include the personality of the da'iyah, the depth of their religious knowledge, as well as community support and the existence of religious study groups. Constraining factors include patriarchal culture, time constraints and mobility limitations of da’iyah, and insufficient oversight from the Islamic Sharia Department. This study emphasizes the importance of optimizing the role of da’iyah in border areas to strengthen Islamic da’wah responsive to women’s issues, as well as the need for sustained structural support from the government and society.